(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article describes an analysis of non-contact optical methods for monitoring linear wear and the working surface condition of the grinding wheel during dry grinding. The presented methods are based on computer processing of photo and video materials, 3D models surface construction of the grinding wheel, the machine vision and using of the optical equipment. The advantages and disadvantages of this methods were analyzed. As a result of the conducted research, it was concluded that the usable area of the considered methods depends on the circle material, cutting parameters, control objectives, including the requirement for on-line control, and also the available material and technical equipment.